ICU nurses’ knowledge and attitude towards electrocardiogram interpretation in Fujian province, China: a cross-sectional study - Salome E. Buluba; Jinyi He; Jinyi He; Hong Li (Frontiers in Medicine, 2023)
IntroductionThe series of electrocardiograms (ECGs) can help track cardiac abnormalities in patients’ conditions and make an earlier clinical decision. It is crucial for nurses working in critical care environments to acquire ECG knowledge for effective ECG monitoring and act accordingly in case of a change in patient condition. This study aimed at investigating intensive care unit (ICU) nurses’ knowledge and attitude towards ECG interpretation in Fujian province, China. The study also analyzed the relationship between participants’ demographic characteristics and level of ECG knowledge.MethodsThis study was done online at twenty-one hospitals in Fujian province using a quantitative cross-sectional design involving 357 registered nurses working in the ICU between October and December 2021. The selection of hospitals and potential participants involved purposive and convenient sampling methods, respectively. Binary logistic regression was carried out to determine factors that predict ICU nurses’ knowledge of ECG interpretation, and a p-value <0.05 was deemed statistically significant.ResultsThe majority of nurses (70.9%) demonstrated a low level of ECG knowledge. The mean score for ECG knowledge was 5.95 (SD = 2.14), with only 0.8% of ICU nurses answering all questions correctly. The majority portrayed positive attitude towards ECG interpretation; however, more than half (61.6%) believed that nurses should rely on a doctor’s opinion about ECG interpretation. Previous ECG training (AOR = 3.98, 95% CI: 2.12–7.45); frequency of ECG interpretation in comparison with no frequency of ECG interpretation (1–3 times per day: AOR = 15.55, 95% CI: 6.33–38.18; 1–3 times per week: AOR = 18.10, 95% CI: 6.38–51.34); and current working unit in comparison to those working in cardiac ICU (general ICU: AOR = 0.45, 95% CI: 0.21–0.94; medical ICU; AOR = 0.28, 95% CI: 0.12–0.67; and surgical ICU; AOR = 0.05, 95% CI: 0.01–0.43) remained statistically significant after adjusting for confounders.ConclusionThe present study revealed a low level of knowledge about ECG interpretation among ICU nurses. Although the participants demonstrated positive attitudes toward ECG interpretation, the negative attitude still existed. Nurses should acknowledge ECG interpretation as part of their duties and responsibilities in nursing care instead of merely relying on doctors’ opinions.